Mary Tudor : Bloody Mary - Maurer, Gretchen (Thinking girl's treasury of dastardly dames., 2011)
Explores this real-life monarch who was at once a great yet brutal leader, detailing her day-to-day life and pivotal moments in the House of Tudor.